Guest

if (m+2)sin(theta) +(2m-1)cos(theta) = 2m+1, then show that tan(theta)=2m+m^2-1

if (m+2)sin(theta) +(2m-1)cos(theta) = 2m+1, then show that tan(theta)=2m+m^2-1

Grade:11

1 Answers

Rituraj Tiwari
askIITians Faculty 1792 Points
one year ago
657-757_Annotation 2020-08-04 210859.png657-2320_Annotation 2020-08-04 211004.png

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free